Key Factors Influencing Adoption of Technology Innovation among Cooperatives in Bandung: A Case of Nectico (The Indonesian Journal of Business Administration, 2020)
In this era, free market competition has raised many challenges that must be faced by economic actors including cooperatives which its development is still small compared to other business entity which have big scale business. Therefore, to face this challenge and survive in the free-market competition era, innovation in cooperative is needed to increase their efficiency and performance. For Nectico, as startup that provides innovative technology which is platform for cooperative to connect them to digital ecosystem, Nectico need to identify and understand key factors that shape the behavioral intention of their customers is needed to formulate strategy that will drive the adoption of technology innovation.Because of that, the objective of this paper is to acquire underlying knowledge of how IT is adopted in cooperative and what factors influence organizational decisions on IT innovation adoption. Besides, this study also has another objective, which is to explore business based on those factors that Nectico could implement to drive more adoption of its innovative technology and propose an implementation plan that is relevant to the business solutions for Nectico.This study is using qualitative data collection through in-depth-interview with key customers and the result of in-depth interview then being verified through a simplified quantitative data collection from cooperatives in Bandung. The result from quantitative data collection is then analyzed from managerial implications point of view which will be used to develop potential business solution and develop implementation plan. This study also suggests the recommendation for further studies.As the result, this study proposed an extended UTAUT for B2B context to illustrate primary adoption of technology innovation. This study also concluded 4 key factors influencing primary adoption of technology innovation among cooperatives in Bandung together with 5 business solutions.Keywords: Innovation; Technology; Adoption; Cooperatives; Organization